Hospital solid waste management strategies to prevent healthcare-associated infections from occupational exposure to bloodborne pathogens and improve occupational safety - Ibáñez-Cruz, Augusto Jorge Antonio; Vergara-Florián, Alejandra Micaela Elena; Algoner, William C. (Frontiers in Public Health, 2025)
Improving occupational safety and public health is crucial to reducing nosocomial infections in healthcare workers due to the ongoing deficiencies in solid waste management in private clinics. For this reason, it is necessary to implement appropriate solid waste management practices to mitigate risks for clinical staff, patients, and the environment. This research focused on reducing the risk of nosocomial infections in healthcare workers exposed to bloodborne pathogens. It was carried out at the private clinic and concentrated on properly managing hospital solid waste, with special attention to occupational health and safety. 400 health workers were trained online during six sessions, addressing biosafety, conditioning, segregation, storage, collection, and transportation of solid waste. The amount of waste produced in kilograms daily was 232.76 bio-contaminated, 11.23 special, and 218.58 joint. Bio-contaminated waste included patient care, bags with human blood and blood products, surgical and anatomicalpathological waste, sharps and biological objects, pharmaceuticals, and hazardous and radioactive chemicals. Proper solid waste management, supported by adequate training, contributed to a significant decrease in the incidence of nosocomial infections: two cases were reported in August and one in September, and there was no incidence of cases from October to December. The estimation of the method used for solid waste disposal showed an acceptable degree in the stages of conditioning, segregation, primary storage, internal transport within the clinic, and central storage. In addition, the occupational health and safety of the personnel at the private clinic was improved.